Patch Testing for Cheilitis: A 10-Year Series. Issue 6 (November 2019) - Cheng, Harriet S.; Konya, Joseph; Lobel, Edmund; Fernandez-Penas, Pablo
Abstract : Background: The etiology of cheilitis includes endogenous, irritant, and allergic dermatitis; lichenoid and granulomatous disorders; infection; trauma; and actinic damage. Patch testing is indicated for refractory cases (other than actinic cheilitis). Objective: The aim of the study was to review demographics and allergens in patients patch tested for cheilitis at 2 sites in Sydney, Australia. Methods: Records for patients patch tested for a 10-year period from 2007 to 2017 were reviewed. Baseline characteristics and patch test results were compared for patients with and without cheilitis. Conclusions: There were 1584 patients including 91 with cheilitis. Patients with cheilitis were more likely to be female, younger, and atopic and have concurrent eyelid involvement than those presenting with other dermatoses. Seventeen percent of patients with cheilitis had a post–patch test diagnosis of allergic contact cheilitis, and the most frequent relevant reactions were to patients' own products, fragrances, and sunscreens. Those with cheilitis had more positive reactions to sunscreens, especially benzophenones, compared with those without cheilitis ( P < 0.001). This is an important finding in Australia where high rates of melanoma and nonmelanoma skin cancer necessitate promotion of strict sun protection measures.